Degradation Mechanism and Stability Improvement Strategy for an Organic Laser Gain Material 4, 4′‐Bis[(N‐carbazole)styryl]biphenyl (BSBCz). (21st January 2019) - Matsushima, Toshinori; Yoshida, Seiya; Inada, Ko; Esaki, Yu; Fukunaga, Toshiya; Mieno, Hiroyuki; Nakamura, Nozomi; Bencheikh, Fatima; Leyden, Matthew R.; Komatsu, Ryutaro; Qin, Chuanjiang; Sandanayaka, Atula S. D.; et al.
Abstract: The organic material 4, 4′‐bis[( N ‐carbazole)styryl]biphenyl (BSBCz) is an excellent gain medium for laser devices. However, BSBCz laser output quickly degrades during photoexcitation, which is an issue that must be overcome before it can be used for practical applications. In this study, the photodegradation mechanisms of BSBCz are investigated with the aim of enhancing its excited‐state stability. The photodegradation of BSBCz is attributed to instability of the triplet excited states that would occasionally decompose into other species. This decomposition reduces absorption and introduces exciton quenchers. Incorporating the triplet managing material 9, 10‐di(naphtha‐2‐yl)anthracene (ADN) into BSBCz films greatly improves photoluminescence and amplified spontaneous emission stability because of the effective removal of the unstable triplets by ADN. This triplet managing method makes it possible to increase operational stability for BSBCz‐based organic light‐emitting diodes. Therefore, these results will contribute toward the fabrication of stable optically and electrically pumped organic laser diodes. Abstract : Photodegradation of a laser gain material 4, 4′‐bis[( N ‐carbazole)styryl]biphenyl (BSBCz) is based on instability of the triplet excited states. Incorporation of 9, 10‐di(naphtha‐2‐yl)anthracene (ADN) into BSBCz films makes it possible to remove the unstable triplets, with radiative singlets of BSBCz being intact. This triplet managing method can greatly improve the excited‐state stability of BSBCz films under both optical and electrical excitations.